Abnormal courtship conditioning in males mutant for the RI regulatory subunit of Drosophila protein kinase A. - O'Dell, K; Jamieson, D; Goodwin, S; Kaiser, K (1999)
The previously described site-selected P-element mutagenesis of a Drosophila gene encoding the regulatory subunit of cAMP-dependent protein kinase generates mutants that have defective behavior in the olfactory learning test. Here we describe the effect of the same mutations in a courtship conditioning assay. Wild-type males can distinguish between virgin females (which they court vigorously), and fertilized females (which they court less vigorously). After exposure to fertilized females, wild-type males modify their behavior by decreasing courtship to subsequent target virgins, an effect that may last for many hours. Like wild-type males, PKA-RI mutant males are also able to distinguish between virgin and fertilized females. PKA-RI males also modify their behavior towards virgin females after prior exposure to a fertilized female, but such an effect is short-lived, suggesting a defect in memory rather than learning. We also show that under these conditions the behavior of PKA-RI males is similar to that of amnesiac, dunce and rutabaga males.